Occurrence of risk factors for endometriosis among women diagnosed laparoscopically for infertility or pelvic pain: authors’ own material - Szubert, Maria; Wierzbowski, Tomasz; Suzin, Jacek; Kowalczyk-Amico, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction: Endometriosis is a chronic disease, very common among women of the reproductive age. This condition can also occur among adolescents and after menopause. Knowledge about real epidemiology of endometriosis will facilitate the diagnostic process. Objectives : To assess the frequency of occurrence of endometriosis and to establish risk factors among women diagnosed laparoscopically for infertility or pelvic pain. Material and methods: 103 women consecutively diagnosed during laparoscopy between May and November 2010 in our department due to the pelvic pain syndrome, suspicion of endometriosis or infertility. The diagnosis of endometriosis was established using rASRM 1996 classification (The Revised American Society for Reproductive Medicine classification of endometriosis). Data were collected from questionnaires with closed questions. Statistical analysis was conducted using Statistica 7.0. Results: Among 103 patients, endometriosis was confirmed in 68.9% of women. Familial occurrence was established in 7% of women. The group of patients with endometriosis significantly more frequently complained of dysmenorrhoea and was taking oral analgesics during menses. Significant difference between groups was also observed for barrier contraceptive methods. There was no significant difference in taking oral contraceptives, coffee drinking, smoking and co-morbidities between the study and control group. Conclusions : Women with endometriosis have a higher risk of painful menstruations and side effects of analgesics used to reduce pain. There is a need for re-evaluation of the diagnosis of functional disorders of the gastrointestinal- and urinary tract after proper diagnosis and treatment of endometriosis.